Comparative impact analysis of laser radiation on steel grades 1045 and 5140; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Lobankova O. V. Olga Vladimirovna (2014, 2014)
Title screen